Clinical and cost-effectiveness of progressive exercise compared with best practice advice, with or without corticosteroid injection, for the treatment of rotator cuff disorders: protocol for a 2x2 factorial randomised controlled trial (the GRASP trial). Issue 7 (17th July 2017) - Hopewell, Sally; Keene, David J; Maia Schlüssel, Michael; Dritsaki, Melina; Dutton, Susan; Carr, Andrew; Hamilton, William; Hansen, Zara; Jaggi, Anju; Littlewood, Chris; Soutakbar, Hessam; Heine, Peter; et al.
Abstract : Introduction: Shoulder pain is very common, with around 70% of cases due to disorders of the rotator cuff. Despite widespread provision of physiotherapy, there is uncertainty about which type of exercise and delivery mechanisms are associated with best outcomes. There is also uncertainty around the long-term benefits and harms of corticosteroid injection therapy, which is often used in addition to physiotherapy. The Getting it Right: Addressing Shoulder Pain trial will assess the clinical and cost-effectiveness of individually tailored, progressive exercise compared with best practice advice, with or without corticosteroid injection, in adults with a rotator cuff disorder. Methods and analysis: We are conducting a large multicentre randomised controlled trial (2×2 factorial design). We will recruit adults ≥18 years with a new episode of shoulder pain attributable to a rotator cuff disorder as per British Elbow and Shoulder Society guidelines, not currently receiving physiotherapy or being considered for surgery, from at least eight UK National Health Service primary care-based musculoskeletal and related physiotherapy services. Participants (n=704) will be randomised (centralised computer-generated 1:1:1:1 allocation ratio) to one of four interventions: (1) progressive exercise (≤6 physiotherapy sessions); (2) best practice advice (one physiotherapy session); (3) corticosteroid injection then progressive exercise (≤6 sessions) or (4) corticosteroid injection then best practice advice (one session). The primary outcome is the mean difference in Shoulder Pain and Disability Index (SPADI) total score at 12 months. Secondary outcomes are: pain and function SPADI subdomains; health-related quality of life (Five-Level version of the EuroQol EQ-5D-5L); sleep disturbance; return to activity; global impression of change; health resource use; out-of-pocket expenses; work disability. A parallel within-trial economic evaluation will be conducted. The primary analysis will be intention to treat. Ethics and dissemination: Research Ethics Committee approval (REC: 16/SC/0508) has been obtained. Results of the main trial and secondary outcomes will be submitted for publication in a peer-reviewed journal. Trial registration number: ISRCTN16539266; EudraCT number: 2016-002991-28.